2013
DOI: 10.1080/08959285.2013.795573
|View full text |Cite
|
Sign up to set email alerts
|

Examining the “Pros” and “Cons” of TeamConflict: A Team-Level Meta-Analysis of Task, Relationship, and Process Conflict

Abstract: Jehn (e.g., 1997) offered three distinct types of team conflict, namely, task conflict, relationship conflict, and process conflict. Despite existing meta-analyses, there remain important and ongoing issues that warrant further meta-analytic investigation. Our contribution is threefold. First, we report novel meta-analytic findings involving moderators of the conflict-team performance relationship. Second, we report on meta-analytic correlations involving all three conflict types and team innovation. Third, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
205
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(221 citation statements)
references
References 110 publications
3
205
3
3
Order By: Relevance
“…Role clarity has been found to be an important factor increase employee performance (e.g., Jackson and Schuler, 1985;Shoemaker, 2003), and has been found to has a positive and significant impact on organizational commitment, employee job satisfaction (e.g., Teas, 1980), reduced job-related tension, lower burnout, lower turnover intensions, satisfaction with co-workers (e.g., Foote et al, 2005;Bauer et al, 2007;Agnihotri et al, 2012). However, existing studies of role conflict and clarity of role thus far has been limited to work roles (e.g., supervisors, managers) in organizations and have not yet conducted regarding roles in interdependent work groups (Beauchamp and Bray, 2001;O'Neill et al, 2013). Klein at al.…”
Section: Uluslararası İktisadi Ve İdari İncelemeler Dergisimentioning
confidence: 99%
“…Role clarity has been found to be an important factor increase employee performance (e.g., Jackson and Schuler, 1985;Shoemaker, 2003), and has been found to has a positive and significant impact on organizational commitment, employee job satisfaction (e.g., Teas, 1980), reduced job-related tension, lower burnout, lower turnover intensions, satisfaction with co-workers (e.g., Foote et al, 2005;Bauer et al, 2007;Agnihotri et al, 2012). However, existing studies of role conflict and clarity of role thus far has been limited to work roles (e.g., supervisors, managers) in organizations and have not yet conducted regarding roles in interdependent work groups (Beauchamp and Bray, 2001;O'Neill et al, 2013). Klein at al.…”
Section: Uluslararası İktisadi Ve İdari İncelemeler Dergisimentioning
confidence: 99%
“…For example, Tjosvold et al (2003) showed that a positive attitude to conflict is positively related to collaborative interaction in teams. Some studies have found a negative relationship between conflict and collaboration (Duarte and Davies in Dietrich et al, 2010), while others also emphasise the positive aspects of conflicts (Vaaland and Håkansson, 2003) as task conflict has a beneficial effect on the performance of decision-making teams (O'Neill et al, 2013). De Dreu and Weingart (2003) executed meta-analysis on the effects of relational and task conflicts on team performance and team member satisfaction and found that both of these conflict types are negatively…”
Section: Relationships Factormentioning
confidence: 99%
“…A prominent case is the phenomenon of intragroup disagreements or confrontations, hitherto interpreted and intensively researched in the context of team or group conflict. The output is a partially contradictory and inconsistent body of knowledge [16,51,75], failing to provide clear prescriptions regarding collaboration engineering and the design of appropriate support systems. The insufficiency may hails from the inadequate framing of relevant findings.…”
Section: Introductionmentioning
confidence: 99%